Addressing sovereign debt challenges in the era of COVID-19 and beyond: The role of the United Nations - Alberto Isgut (Asia-Pacific Sustainable Development Journal, 2022)
Traditionally, sovereign debt problems of developing countries have been discussed mostly at institutions representing the creditors, such as the Paris Club, and at the International Monetary Fund, but they have also been addressed by the United Nations, mostly in the context of its international conferences on financing for development. Although the views of the United Nations on debt are not widely known, they are highly relevant in the post-COVID-19 context, as inflationary pressures could lead to tightened global financial conditions and exacerbate debt vulnerabilities in developing countries. The present paper provides an overview of sovereign debt restructurings from the 1980s, a summary of the debt situation of Asia and the Pacific as a case study and a review of the views of United Nations on debt issues. It also offers suggestions to improve the global debt architecture based on such views by highlighting the importance of linking debt sustainability with sustainable development in debt restructuring workouts and through a hub-and-spoke institutional arrangement to disseminate prudential debt management practices and promote transparency.